PHYSICAL PROFILE (skill time) AND PERFORMANCE OF SOME CONDITIONING CAPACITIES (skill reach) OF THE MASTER VOLLEYBALL DURING THE SETS - Nelson Kautzner Marques Junior (Federación Extremeña de Balonmano; University of Extremadura, 2018)
The objective of the study was to analyze of each set the physical profile (attack ball time, serve ball time and setter time) and some conditioning capacities (block reach, block jump, spike reach and spike jump). The study was composed of 15 matches of the male master volleyball of the category 35 years or more. The data were collected with the camera in a gymnasium. After the data collected, the researcher practiced the physical performance analysis with the Kinovea® software and wrote on a scout. Kruskal Wallis ANOVA did not identify statistical difference during each set of the block reach [H (2) = 5,66, p = 0,05], of the spike reach [H (2) = 3,45, p = 0,17], of the attack ball time [H (2) = 4,08, p = 0,12], of the serve ball time [H (2) = 2,51, p = 0,28] and of the setter time [H (2) = 2,39, p = 0,30]. The new statistic did not identify a statistical difference of the physical performance data (block and spike reach, attack and serve ball time and the setter time). In conclusion, the analysis of the physical performance during each set is important to guide the physical training.